Predictors of in-hospital mortality in a cohort of elderly Egyptian patients with acute upper gastrointestinal bleeding - Elsebaey, Mohamed A. (Medicine (Baltimore), 2018)
Acute upper gastrointestinal bleeding (UGIB) affects large number of elderly with high rates of morbidity and mortality. Early identification and management of the factors predicting in-hospital mortality might decrease mortality. This study was conducted to identify the causes of acute UGIB and the predictors of in-hospital mortality in elderly Egyptian patients. 286 elderly patients with acute UGIB were divided into: bleeding variceal group (161 patients) and bleeding nonvariceal group (125 patients). Patients’ monitoring was done during hospitalization to identify the risk factors that might predict in-hospital mortality in elderly. Variceal bleeding was the most common cause of acute UGIB in elderly Egyptian patients. In-hospital mortality rate was 8.74%. Increasing age, hemodynamic instability at presentation, co-morbidities (especially liver cirrhosis associated with other co-morbidity) and failure to control bleeding were the predictors of in-hospital mortality. Increasing age, hemodynamic instability at presentation, co-morbidities (especially liver cirrhosis associated with other co-morbidity) and failure to control bleeding should be considered when triaging those patients for immediate resuscitation, close observation, and early treatment.